(untitled) (Periphērica, 2023)
The last years of José Martí in the United States can be classified as one of the author’s most prolific intellectual periods in terms of race. In the 1890s, he published several articles on the subject as his activism for the liberation of the island gained decisive momentum. With this work we try to illustrate how Martí’s position regarding the racial issue evolved towards carrying out concrete actions, such as the foundation in 1892 of the Partido Revolucionario Cubano (PRC). The analysis is drawn mainly from a series of texts published in the Patria newspaper, the ideological organ of the PRC. Between 1892 and 1894, this publication was the platform that Martí used to prepare and promote the social scenario that he envisioned for the construction of post-colonial Cuba, encouraging racial inclusion and civil participation stemming from his political agenda.